Impact of Neoliberal Educational Policies on Equity and Teaching Practices. A Case Study in Two Secondary Schools - Martín-Alonso, Diego; Guzmán-Calle, Eva (My University, 2021)
Different international organizations and strategies for the unification of educational objectives and policies have been promoting a global educational agenda (GEA onwards) in recent decades that is oriented towards an educational transformation that seeks cultural homogenization, the reinforcement of the labor market and reforms based on a sustainable, efficient and quality investment. As other works point out, these educational policy reforms that seek to transform the organization and management of schools are carried out by introducing the postulates of the economics of education and management into the educational system. business; so we could call it a “neoliberal pedagogy”. Based on previous studies, these policies end up configuring a new educational control model focused on efficiency and results that have been called performativity technology. This is, synthesizing, that both teachers and students should guide their efforts to get as close as possible to achieving the standards established by the educational administration. Within this framework, and within a broader research project we intend to deepen in different educational contexts of several regions in Spain. Specifically, in this proposal we present the study carried out in two public high schools in Andalucía (Spain), where educational innovation projects have been promoted in recent years.
Keywords: Política educativa